Community perceptions and practices in malaria and development of an educational intervention conducted in an endemic area of Colombia (2022)
ABSTRACT: Malaria prevention and control programs have primarily targeted the Anopheles mosquito vector, but this disease encompasses biological components and social aspects thus, the design of prevention and control strategies should consider community beliefs and practices 1 2 Therefore, the aim of this study was to determine the knowledge, attitudes and practices ( towards malaria in a community of a Colombian endemic area The information identified through the KAPs survey contributed to the design of education strategies for malaria prevention and control they have previously shown to enforce community adherence to achieve sustainable control.